Conte outras histórias que sejam nossas : a temática indígena e a Lei n. 11.645/2008 nos livros didáticos de História no ensino médio, uma análise da coleção História em Debate - Coimbra, Luzia Aparecida Gonçalves (2020)
The present thesis aims to analyze how indigenous peoples portray in didactical History books from the collection Coleção História em Debate, which the Brazilian National Program for the Didactic Books (PNLD) approved in 2018 and designed to High School students. It intends to identify disruptions and stereotypes permanency after approval of Law no. 11.645/2008, which makes mandatory teaching Indigenous Culture in Elementary Schools nationwide. Besides new content included in the Basic Education Curriculum in Brazil, we can also mention the new paths that History teaching has taken to break traditional concepts and foment critical observations about History. The National Curriculum Parameters (PCN) created in 1990, for instance, encouraged History teaching through a thematic axis. The development of the research occurred through qualitative investigation within a data survey, which referred to didactic books in Brazil and their handling with indigenous thematics. The enormous interest in Indigenous Ethnology and the possibility to sharing new knowledge to a broad audience motivated this research.